Peran Mambaul Ulum dalam Menyebarkan Pendidikan Agama Islam di Surakarta - Rizqi Al-Ali, Muhammad; Al Mubarak, Fatwa; Faqihuddin Rifa’i, Habib; Ali, Haidar (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2025)
Mambaul Ulum, an Islamic educational institution in Surakarta, has played an important role in spreading Islamic religious education in the city for more than a century. Founded in 1905, Mambaul Ulum has produced many Muslim scholars and intellectuals who have made significant contributions to the development of Islam in Indonesia. This journal aims to discuss the role of Mambaul Ulum in spreading Islamic religious education in Surakarta. This journal is the history and development of mabaul ulum, mabaul ulum educational methods, the role of mabaul ulum in Islamic religious education in Surakarta, the influence of mabaul ulum on society in Surakarta. The research method used in this journal is qualitative research with a historical approach. Data was collected from various sources, including Mambaul Ulum archives, books, journals and previous research results. The data was then analyzed descriptively and interpretively. The research results show that Mambaul Ulum has played an important role in spreading Islamic religious education in Surakarta. This institution has produced many Muslim scholars and intellectuals who have made significant contributions to the development of Islam in Indonesia. Mambaul Ulum has also contributed to the development of Islamic education in Indonesia, by developing an educational curriculum that is modern and relevant to the needs of the times. Keyword: Mambaul Ulum, Islamic religious education, Surakarta, Indonesia.